Trekking the Post-COVID Terrain: Unearthing Online Business Evolution - Mayasari, Sephia; Mediawati, Noor Fatimah; Rositasari, Dewi (Proceedings of The ICECRS, 2023)
This data article presents a meticulous analysis of scholarly works on "Online Business AND Post-Covid" sourced from Lens.org. Employing keyword-based searches and precise filtering for document types and subject matter (Law), it gathered relevant journal articles and conference proceedings, exporting data in CSV and BIBTEX formats, alongside image extractions. Findings spotlight key insights, such as the University of Leeds' prominent contribution, the prolific year of 2020, and prevalent subject areas like Political Science and Pandemic. Active institutions like the University of Sheffield and the dominance of the United Kingdom as the most active country emerge. This dataset serves as a crucial resource for researchers, enabling further investigations and experimentation in the evolving landscape of online business post-Covid.Highlights: Detailed analysis of scholarly works on Post-Covid Online Business from Lens.org. Highlights key contributors, prolific years, and prevalent subject areas. Offers valuable resources for researchers exploring the evolving field of online business post-Covid. Keywords: Online Business, Post-Covid, Scholarly Analysis, Research Resources, Data Insights